Dynamics of power relations between village governments and tourism actors in poverty alleviation in the Mandalika Special Economic Zone - Subriati Subriati; Daezah Rani; Nurlia Nurlia; Dinda Dinda; Sripe Wafiq Azizah; Muliatun Anisa; Ita Aulia; Nurul Anggriani; Inka Nusamuda Pratama (Privietlab, 2026)
Mandalika Special Economic Zone (SEZ) and examine its implications for the formulation and implementation of poverty alleviation policies at the local level. This study uses a qualitative approach with a critical perspective aimed at uncovering power structures, patterns of domination, and inequality in relations between actors in area-based tourism development. The research location is in Kuta Village, Pujut District, Central Lombok Regency, with informants selected purposively, including village governments, local governments, investors or area managers (ITDC), and poor communities. Data collection was conducted through in-depth interviews, participatory observation, and analysis of policy documents. While data analysis used power mapping and thematic analysis techniques. The results show that power relations in the management of the Mandalika SEZ tend to be unbalanced and dominated by the central government and investors, thus limiting the space for village government participation in the decision-making process. This condition has implications for the suboptimal implementation of poverty alleviation policies and the unequal distribution of development benefits at the local level. Furthermore, the findings indicate that some communities remain vulnerable despite the region's tourism sector growth. Therefore, this study confirms the existence of unequal power relations that influence the effectiveness of development policies, while also identifying a research gap related to the limited studies focusing on negotiation mechanisms and resistance from local actors in area-based tourism development governance.